Supraorbital Keyhole Approach—A Minimally Invasive Versatile Approach to Skull Base Lesions - Pai, Balaji S.; Khandelwal, Sandesh; Narayana, Vishwanath; Maulyavantham Nagaraj, Nagarjun (Indian Journal of Neurosurgery, 2023)
Background Over the last two decades, there have been development of approaches that are minimally invasive but achieve maximum effective results with minimal morbidity. The supraorbital keyhole approach (SOKHA) through the transciliary incision is minimally invasive approach that permits effective management of skull base lesions with minimal injury to the soft tissue and surrounding brain.Aims The aim of this study was to evaluate the efficacy and safety of SOKHA for skull base lesions.Settings and Design This is a prospective study in a tertiary neurosurgical teaching institute in a metropolitan city.Materials and Methods Twenty-one patients of various pathology were operated using the SOKHA through the “eye-brow incision.” The pathologies included pituitary adenoma, craniopharyngioma, epidermoid, tuberculum sella, and planum sphenoidale meningioma. The authors describe in detail the surgical approach employed by them for these various pathologies.Results All neoplastic lesions in this series could be addressed effectively with near total or total excision. No fresh postoperative deficits were noted except a case who developed ipsilateral anterior cerebral artery infarction that resulted in lower limb weakness. One patient developed postoperative abscess requiring surgical excision. At follow-up, all patients revealed a cosmetic scar hidden by the eye brow.Conclusion The SOKHA is an effective minimally invasive procedure with proven safety for the management of anterior, selected middle skull base lesions and to provide excellent cosmesis with minimal trauma to the adjacent brain. The authors, however, feel that it is technically demanding and surgeons should employ a stepwise progression from simple to more complex lesions.
Keywords: transciliary incision; keyhole surgery; supraorbital approach; minimally invasive neurosurgery approach; frontoorbitotomy